A Wayside Shrine in Northern Moab. Excavations in the Wadi Ath-Thamad - P. M. Michele Daviau; Margreet L. Steiner (Les Carnets de l’ACoSt)
An isolated Iron-Age shrine at Wadi ath-Thamad Site WT-13 in northern Moab contained numerous finds of figurines and statues that contribute to our understanding of repeated cultic activities at the site.